IMPLEMENTASI NEUROFISIOLOGIS DAN NEUROSAINS DALAM PENGEMBANGAN KARAKTER BAGI PESERTA DIDIK DI ASRAMA - NURAENI, DEWI; WASEHUDIN, WASEHUDIN; HABUDIN, HABUDIN; LAZZAVIETAMSI, FANDY ADPEN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to explore neurophysiological and neuroscientific theories and analyze their relevance in the context of Islamic education. Using qualitative methods, this article systematically focuses on the relationship between neural stimulation and the formation of behavioral patterns. Apart from that, this research also explores the application of neuroscience theory in the development of Islamic education. A thorough analysis of these concepts reveals a significant balance between neurophysiological theory and the principles of Islamic education which emphasizes increasing spiritual and intellectual understanding. The results of this research provide an important contribution to the development of scientific and neuroscience-based Islamic education, by highlighting the importance of understanding the neurophysiological mechanisms underlying learning processes and spiritual development in religious contexts. The theoretical and practical implications of this research can provide a strong foundation for the development of innovative and effective learning methods in Islamic education, which can increase students' spiritual and intellectual understanding and awareness. ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi teori neurofisiologis dan neurosains serta menganalisis relevansinya dalam konteks pendidikan Islam. Dengan menggunakan metode kualitatif, artikel ini secara sistematis fokus pada keterkaitan antara stimulasi saraf dan pembentukan pola perilaku. Selain itu, penelitian ini juga mengeksplorasi aplikasi teori neurosains dalam pengembangan pendidikan Islam. Analisis menyeluruh terhadap konsep-konsep tersebut mengungkapkan keseimbangan yang signifikan antara teori neurofisiologis dengan prinsip-prinsip pendidikan Islam yang menekankan pada peningkatan pemahaman spiritual dan intelektual. Hasil dari penelitian ini memberikan kontribusi penting terhadap pengembangan pendidikan Islam yang berbasis ilmiah dan neurosains, dengan menyoroti pentingnya memahami mekanisme neurofisiologis yang mendasari proses pembelajaran dan perkembangan spiritual dalam konteks agama. Implikasi teoritis dan praktis dari penelitian ini dapat memberikan landasan yang kuat bagi pengembangan metode pembelajaran yang inovatif dan efektif dalam pendidikan Islam, yang dapat meningkatkan pemahaman dan kesadaran spiritual serta intelektual para pelajar.